1996
DOI: 10.1021/jp9606321
|View full text |Cite
|
Sign up to set email alerts
|

Specific Adsorption of a Bisulfate Anion on a Pt(111) Electrode. Ultrahigh Vacuum Spectroscopic and Cyclic Voltammetric Study

Abstract: We addressed in this study the process of specific adsorption of anions at the metal/solution interface. We focused on the nature of the surface chemical bond that accounted for the phenomenon of adsorption specificity in the context of bisulfate coverage and structural information. While we limited our investigations to bisulfate adsorption on the Pt(111) electrode in sulfuric and mixed sulfuric/perchloric acid media, our conclusions have general significance in explaining ionic adsorption events in electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 84 publications
6
96
1
1
Order By: Relevance
“…Cyclic voltammogram (CV) measurements on the PVPA-wrapped and non-wrapped composites were carried out in 0.1 M HClO 4 aqueous solutions3132. The electrochemical surface area (ECSA) of the Pt nanoparticles of the MWNT/PVPA-PyPBI/Pt was evaluated to be 40.2 m 2 /g, which is lower than that 51.6 m 2 /g of the MWNT/PyPBI/Pt23 (see Supplementary Information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic voltammogram (CV) measurements on the PVPA-wrapped and non-wrapped composites were carried out in 0.1 M HClO 4 aqueous solutions3132. The electrochemical surface area (ECSA) of the Pt nanoparticles of the MWNT/PVPA-PyPBI/Pt was evaluated to be 40.2 m 2 /g, which is lower than that 51.6 m 2 /g of the MWNT/PyPBI/Pt23 (see Supplementary Information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the stripping of the solvation shell upon discharge and formation of the bond with the surface, there is an activation barrier for this process leading to a limited rate of this process. Examples are the adsorption of iodide, bromide and sulfate on Pt and Au single crystal electrodes [17,18,22,23,28,40,[76][77][78][79] Also upd systems and proton adsorption e. g. on Pt belong to this category. The potential dependence leads to adsorption peaks in cyclic voltammograms (or capacitance peaks in AC-voltammetry), the peaks of which shift by ca.…”
Section: Discussionmentioning
confidence: 99%
“…Cation/anion effects.─ Electrolyte components can significantly influence the activity of a given electrocatalyst, even if they are seldom regarded as being directly involved in the catalytic process of interest. As an example, the influence of cations and anions on the oxygen reduction activity of Ptelectrodes has been widely studied [169][170][171], but equivalent studies dealing with their effects on the OER-kinetics are still rare. Ganassin et al [172] grew Ir-oxide films on Ir(111) and observed a decrease of their OER performance upon transitioning from 0.1 M HClO 4 to 0.05 M H 2 SO 4 ; the authors related this behavior to a delay in the oxidation of the metallic surface and a corresponding shift of the OER towards more positive potentials, induced by the presence of HSO 4 -/ SO 4 2anions.…”
Section: The Oxygen Evolution Reactionmentioning
confidence: 99%